Effect of basketball mass on shot performance among 9-11 year-old male players - Arias, J. L.; Argudo, F. M.; Alonso, J. I. (International Journal of Sports Science and Coaching, 2012)
The goal of this study was to analyse with which ball the participants achieved a greater number of shot attempts and successful shots. The participants included fifty-four 9-11 year-old children from six basketball teams. We established three situations in which the participants played four games with each of the following balls: a) regulation (485 g, 69-71 cm); b) ball of smaller mass (440 g, 69-71 cm); and c) ball of greater mass (540 g, 69-71 cm). The results reflected statistically significant differences for the ball possessions in which there was no shot attempt (X²=11.751, df=2, p=.003), for the free throw shot attempts (X²=14.213, df=2, p=.001), the 2-point field goal attempts (X²=6.921, df=2, p=.031), successful free throws (?2=6.273, df=2, p=.043), and successful 3-point field goals (X²=5.545, df=2, p=.05). The highest frequency of shot attempts and successful shots occurred with the ball that had a mass of 440g.